Novel natural and biomimetic ligands to enhance selectivity of membrane processes for solute‐solute separations: beyond nature's logistic legacy. Issue 3 (4th November 2013) - Vanneste, Johan; Peumans, Willy J.; Van Damme, Els J.M.; Darvishmanesh, Siavash; Bernaerts, Kristel; Geuns, Jan M. C.; Van der Bruggen, Bart
Abstract The integration of natural or biomimetic ligands in membrane processes was explored, focusing on simplicity and originality, with an eye to increasing the often moderate selectivity. Due to their simple structure, selection and manufacturing procedure, aptamers could dramatically increase the cost effectiveness of ligand‐based membrane processes. Proteins are distinctly more complex than aptamers, but many excel in organizing selective transmembrane transport. The channel geometry of aquaporins was also found to be tailored for high fluxes by minimizing vortex formation. Incorporation of bacterial porins could tremendously increase the performance of nanofiltration membranes by increasing the rejection of apolar often more toxic compounds. Sugar‐selective porins on the other hand, could be used to manufacture the first chemical‐free membrane adsorber. Ultimately, bacterial strains could be selected, through multiple evolution cycles, which express porins tailored to recognize specific molecules. Lectins are definitely better suited than porins for high resolution carbohydrate purification. Lectins could be used to effectively separate different sugar isomers in one bind and elution step. The potential of Concanavalin A for the purification of the natural sweetener stevioside was explored. A discrimination factor in dissociation constant of a factor 6 and 23 was obtained in silico relative to glucose and mannose respectively. Finally, a new method was discussed from the field of drug design that can determine the selectivity in silico, independent of other competing ligands or targets. The intrinsic selectivity ratio seems to solve an age‐old problem and another possible impediment to swift industrial application of ligand‐based membrane processes. © 2013 Society of Chemical Industry